Effect of Isothermal Treatment on Microstructure and Mechanical Properties of Cold-Deformed IF Steel - Jose Luis Reyes Barragan; Roberto Ademar Rodriguez Diaz; Maria Luisa Ojeda Martinez; Silvia Gaona Jimenez; Julio Alberto Juarez Islas (Advances in Materials Science and Engineering)
In this study, we investigated the recrystallisation kinetics of Ti-stabilised interstitial-free (IF) steel manufactured by the Mexican steel industry through the route of electric arc furnace with vacuum degassing, secondary refining, and subsequent continuous casting. The IF steel was hot-rolled at 950°C and then cold-rolled until deformation of 94% was attained, followed by recrystallisation at different times at a constant temperature of 780°C. In addition, the mechanical properties of the IF steel were assessed as a function of recrystallisation time. The results obtained from the mechanical property tests were presented in the form of plots of microhardness, yield strength, ultimate tensile stress, and deformation percent as functions of the recrystallised fraction with an indirect dependence on recrystallisation time. A graphical model of the recrystallisation behaviour showed the evolution of the microstructure, including phase transformations, hardness, and the mechanical properties determined from the tensile tests. In view of subsequent recovery and recrystallisation, stored energy analysis derived from the strain induced by deformation was presented. Furthermore, we determined the precipitates formed in the different processing stages of IF steel.